Manx speakers, language, and identity - McNulty, Erin (Studia Celtica Posnaniensia, 2023)
Manx, the Goidelic language of the Isle of Man, has no extant traditional native speakers. However, thanks to the efforts of language activists and others involved in language revival, there exists a community of around 2200 people who claim competence in the language (Isle of Man Government 2021), of which a smaller portion will have advanced competence in Manx. All members of the Manx speaker community could be described as ‘new speakers’, having acquired this revitalized minority language primarily through means other than first language transmission in the home (O’Rourke, Pujolar, and Ramallo 2015: 1). The members of the Manx new speaker community, despite many having acquired “a socially and communicatively consequential level of competence” (Jaffe 2015: 25) in the traditional language of the Isle of Man, vary in terms of their national, ethnic, and linguistic backgrounds. Postmodern approaches to sociolinguistics challenge the assumption of a straightforward link between identity, especially national identity, and linguistic practice. The complexity of the elationship between language and identity is especially evident in cases of multilingual minority language communities – such as the extant Celtic-speaking communities. The present paper explores the relationship between identity and language use among Manx new speakers. It discusses the following specific question: How do new speakers of Manx understand and identify with ‘Manxness’? The paper uses a corpus of sociolinguistic interview and ethnographic observation data gathered from fieldwork among the Manx new speaker community as part of the author’s PhD thesis. The researcher, a Manx new speaker herself, spent six months gathering data, both through traditional sociolinguistic methods, such as interviews and questionnaires, and through ethnographic methods, namely participant observation in various contexts. The analysis of this novel spoken corpus offers a much-needed view into identity and language use in a 21st-century Celtic language community that lacks extant native speakers.